Prolapse of the Small Intestine from the Uterine Perforation at Dilatation and Curettage - Shigeki Matsubara; Akihide Ohkuchi; Hiroaki Nonaka; Homare Ito; Alan T. Lefor (Case Reports in Obstetrics and Gynecology)
Dilatation and curettage (D&C) sometimes causes uterine perforation, which usually does not cause a serious problem. Here, we report uterine perforation caused by D&C, in which the small intestine prolapsed from the uterus, requiring intestinal resection. D&C was performed for missed abortion at 9 weeks. After dilating the cervix, forceps grasped tissue that, upon being pulled, resulted in the intestine being prolapsed into the vagina. Laparotomy revealed a perforation at the low anterior uterine wall, through which the ileum had prolapsed. The mesentery of the prolapsed ileum was completely detached and the ileum was necrotic, which was resected. The uterus and the intestine were reconstructed. Although intestinal prolapse is considered to be caused by “unsafe” D&C performed by inexperienced persons or even by nonphysicians in developing countries, this occurred in a tertiary center of a developed country. We must be aware that adverse events such as uterine perforation with intestinal prolapse can occur even during routine D&C.